The Relationship Between Reading Speed and Comprehension: A Diagnostic Study with AceReader - Titin Kustini (English Language Education Department, Universitas Majalengka, 2025)
This diagnostic study investigates the relationship between reading speed and reading comprehension among Indonesian EFL learners, Fourth-semester students of the Communication Science Study Program, Faculty of Social and Political Sciences, using the digital assessment tool, AceReader. Thirteen participants completed three reading texts, each followed by comprehension questions. Reading speed (wpm) and comprehension scores (%) were recorded and averaged. Descriptive analysis revealed mean reading speeds of 107.8, 143.2, and 131.5 wpm across the three texts, and comprehension means of 75%, 55.8%, and 63.5%, respectively. The standard deviation values indicate moderate to high variability in both reading speed and comprehension. Linear regression analysis showed no statistically significant relationship between reading speed and comprehension (R² = 0.005, p = 0.820). These results suggest that reading speed alone does not predict comprehension ability. The study highlights the complexity of reading fluency in EFL contexts and calls for a more integrated approach to reading instruction and assessment.